Case Report: A novel mixture of dose-fractioned radiation and immunotherapy for treatment of cholangiocarcinoma - Wang, Ningyu; Wang, Linfang; Huang, Ai; Han, Jun; Cao, Ting; Mei, Xiangping; Yao, Jing; Xiao, Yong; Ma, Hong (Frontiers in Immunology, 2023)
Malignant tumors of the biliary tract exhibit a high degree of malignancy and heterogeneity with a poor overall prognosis. Immunotherapy has limited benefits for patients with cholangiocarcinoma. Radiation therapy can change the tumor microenvironment, but its effect heavily depends on radiation dose and fraction. We report a case of advanced intrahepatic cholangiocarcinoma in a 43-year-old male patient, with a huge liver mass of 16.5 cm in diameter, with bone and liver metastases at the first diagnosis. First-line treatment with chemotherapy and PD1 inhibitor was sustained only for 8 months. In second-line treatment, radiotherapy was administered, with 5 Gy in 5 fractions administered to the entire tumor area and 25 Gy in 5 fractions to the solid lesions of the tumor. After the completion of radiotherapy, programmed cell death 1 inhibitor combined with tyrosine kinase inhibitor was maintained. The patient achieved a progression-free-survival time of 12 months and an overall survival time of 25 months. The success of our case suggests that mixed low- and high-dose radiation can significantly improve tumor control and survival time. In clinical practice, based on the characteristics of the tumor and existing treatment options, the rational combination of existing treatment regimens can improve the prognosis of cholangiocarcinoma.